Numerical simulation of local bubble size distribution in bubble columns operated at heterogeneous regime. (15th February 2021) - Zhang, Xi-Bao; Yan, Wei-Cheng; Luo, Zheng-Hong
Highlights: Effect of lift force and turbulent dispersion force on local BSD is investigated. Effect of coalescence models and breakup models on local BSD is studied. Effect of parameters in class method for solving PBEs on local BSD is studied. The lift force has strong effect on the local BSD. The minimum and maximum bubble diameters have large impact on local BSD. Abstract: This work investigates the effect of lift force, turbulent dispersion force, bubble breakup models, bubble coalescence models, and the parameters in the class method for solving PBEs on the simulated local bubble size distribution (BSD) at various radial positions (r/R = 0.0, 0.27, 0.58 and 0.8), and the local Sauter mean diameter (Sd ) in bubble columns. The results suggest that the local BSD and Sd are slightly affected by the radial positions but greatly influenced by the lift force and the parameters in the class method (e.g. the minimum bubble diameter and maximum bubble diameter). The prediction of BSD could be promoted by including the lift force. The local Sd increases with the increase of the minimum bubble diameter and the maximum bubble diameter.